Evaluation of the RAPIDEC CARBA NP, Conventional CarbaNP, and the Modified Carbapenem Inactivation Method (mCIM) Tests for Phenotypic Detection of Carbapenemase-Producing Organisms. (21st September 2018) - Walthall, Keandra; Anderson, Karen; Reese, Natashia; Lonsway, David; Kamile Rasheed, J; Karlsson, Maria
Abstract: Decreased susceptibility to carbapenems is being increasingly reported among Gram-negative organisms worldwide. It is of critical importance for patient management and infection control purposes to detect carbapenemase-producing organisms rapidly and reliably. In this study, the performance of the commercially available RAPIDEC CARBA NP test (bioMérieux, Durham, NC) was evaluated against the performance of the conventional CarbaNP and the modified Carbapenem Inactivation Method (mCIM) for the detection of carbapenemase activity in Enterobacteriaceae and Pseudomonas aeruginosa . A total of 73 Enterobacteriaceae and 32 Pseudomonas aeruginosa isolates were tested for carbapenemase activity using the RAPIDEC CARBA NP, conventional CarbaNP, and mCIM methods. Using available whole-genome sequence information, this collection included 72 isolates with and 33 isolates without carbapenemase genes. The isolates harboring a carbapenemase gene encoded 20 class A, 47 class B, and 5 class D–type β-lactamases. All methods were performed using bacteria from a single overnight blood agar plate. The conventional CarbaNP and mCIM were performed according to guidelines from the Clinical and Laboratory Standards Institute. The RAPIDEC CARBA NP was performed per the manufacturer's instructions. The RAPIDEC CARBA NP detected 65 of 72 (90%) carbapenemase-producing isolates; the seven isolates yielding false-negative results included five Enterobacteriaceae with bla OXA-48-like and two with bla KPC-4 genes. The sensitivity and specificity were 90.2% and 100%, respectively, for the RAPIDEC test; 94.4% and 100% for conventional CarbaNP; and 100% and 81.8% for mCIM. The conventional CarbaNP detected all carbapenemase producers except four OXA-48-like–producing isolates. The mCIM, which accurately detected all carbapenemase producers, yielded false-positive results in six isolates of P aeruginosa . Overall, the RAPIDEC CARBA NP was easy to use and required less hands-on time than the conventional CarbaNP and mCIM methods. However, the RAPIDEC CARBA NP showed decreased sensitivity for detecting low-level activity carbapenemases such as OXA-48-like enzymes and KPC-4.